Durability of natural fiber-reinforced composites of ethylene-propylene copolymer under accelerated weathering and composting conditions - Kumar, A. P.; Depan, Dilip; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2005)
Three types of composites are prepared by the melt mixing of ethylene-propylene copolymer (EPC) with (i) 3 % NaOH-treated jute fiber, (ii) 17.5 % NaOH-treated jute fiber, and (iii) commercial microcrystal line cellulose powder using maleated EPC as compatibilizer. The composites obtained are characterized by FTIR and microscopic measurements. Their mechanical properties are measured using a UTM (Instron model 4204). The durability of the composites is evaluated in an irradiation chamber with UV radiation of wavelength lambda >= 290 mn and composting conditions at different time intervals. The composites made from microcrystalline cellulose show superior mechanical properties, biodisintegrability, as well as photoresistance whereas the specimen containing 3% NaOH-treated fiber exhibited the lowest photoresistance. Increasing the quantity of maleated EP (MEP) in the composition decreases photostability. Neat EPC has been found to be highly stable than all the composites with increasing UV irradiation. It has been found that the composites are less durable under both abiotic and biotic conditions in comparison to the neat polymer.
Keywords: compatibilization; composites; jute fiber; mechanical properties; Microcrystalline cellulose; photodegradation and composting

Highly active new alpha-diimine nickel catalyst for the polymerization of alpha-olefins - Liu, Hua-Rong; Gomes, P. T.; Costa, S. I.; Duarte, M. T.; Branquinho, R.; Fernandes, A. C.; Chien, J. C. W.; Singh, R. P.; Marques, Maria M. (Journal of Organometallic Chemistry, 2005)
A new silylated alpha-diimine ligand, bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene 3, and its corresponding Ni(II) complex, {bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene} dibromonickel 4, have been synthesized and characterized. The crystal structures of 3 and 4 were determined by X-ray crystallography. In the solid state, complex 4 is a dimer with two bridging Br ligands linking the two nickel centers, which have square pyramidal geometries. Complex 4, activated either by diethylaluminum chloride (DEAC) or methylaluminoxane (MAO) produces very active catalyst systems for the polymerization of ethylene and moderately active for the polymerization of propylene. The activity values are in the order of magnitude of 10(7) g PE (mol Ni [E] h)(-1) for the polymerization of ethylene and of 10(5) g PP (mol Ni [P] h)(-1) for the polymerization of propylene. NMR analysis shows that branched polyethylenes (PE) are obtained at room or higher temperatures and almost linear PE is obtained at 0 degrees C with 4/DEAC. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: alpha-diimine nickel complex; Ethylene polymerization; late transition-metal; propylene polymerization

Photodegradation of ethylene/propylene/polar monomers co- and terpolymers. I - Prepared by group 4 catalyst systems - Fernandes, Susete N.; Correia, Sandra; Prasad, A. V.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Marques, Maria M.; Singh, R. P. (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
The photooxidative degradation behavior of polyethylene, its copolymers (propylene/polar monomers) and terpolymers, synthesized by a group 4 catalyst system, has been studied by Fourier transform infrared spectroscopy and confirmed with scanning elecrton microscopy for morphological changes. The kinetics of photodegradation has also been studied. Surface damage caused by polychromatic (>= 290 nm) at 55 degrees C in air is presented in different micrographs. The rate of photodegradation is very fast in terpolymers containing polar monomers as compared with copolymers and polyethylene. Morphological study of these photodegraded samples showed a very good relation with photodegradation results.
Keywords: functional polyolefins; Photodegradation; UV irradiation

Recent advances in biodegradable nanocomposites - Pandey, J. K.; Kumar, A. P.; Misra, M.; Mohanty, A. K.; Drzal, L. T.; Singh, R. P. (Journal of Nanoscience and Nanotechnology, 2005)
There is growing interest in developing bio-based products and innovative process technologies that can reduce the dependence on fossil fuel and move to a sustainable materials basis. Biodegradable bio-based nanocomposites are the next generation of materials for the future. Renewable resource-based biodegradable polymers including cellulosic plastic (plastic made from wood), corn-derived plastics, and polyhydroxyalkanoates (plastics made from bacterial sources) are some of the potential biopolymers which, in combination with nanoclay reinforcement, can produce nanocomposites for a variety of applications. Nanocomposites of this category are expected to possess improved strength and stiffness with little sacrifice of toughness, reduced gas/water vapor permeability, a lower coefficient of thermal expansion, and an increased heat deflection temperature, opening an opportunity for the use of new, high performance, lightweight green nanocomposite materials to replace conventional petroleum-based composites. The present review addresses this green material, including its technical difficulties and their solutions.
Keywords: cellulose; layered silicates and properties; Nanocomposite; poly(caprolactone)s; poly(hydroxy alkanoate)s; polyiactic acid; Starch

Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

Synthesis, characterization, and performance evaluation of novel stabilized TDI-based polyurethane coatings under accelerated weathering - Kumar, A. P.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Raut, K. G.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2005)
Some toluene dilsocyanate (TDI)-based polyurethane resins (PURs) for coating applications were synthesized with castor oil and their performance was estimated under accelerated UV weathering with and without a novel UV absorber. Changes in physical properties, chemical structure, and color of the samples were monitored by mechanical property testing, FTIR spectroscopy, and colorimetry, respectively. A stable polyurethane coating was achieved at 0.5% concentration of additive in the host matrix. Mechanical properties were also retained as in the pristine PUR after mixing. Commercial Tinuvin P and benzotriazole-based novel UV absorbers were found to improve the photoresistance of the PUR coating, and the highest efficiency of the novel UV absorber against weathering was estimated at 0.5 wt% concentration.(c) 2005 Society of Plastics Engineers.

Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Biodegradation of gamma-sterilised biomedical polyolefins under composting and fungal culture environments - Alariqi, Sameh A. S.; Kumar, A. P.; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2006)
Polyolefin-based commodities are widely used as biomedical devices and food packaging after gamma-sterilisation. The aim of the present work was to study the effect of gamma-sterilisation on the biodegradation of polyolefins. Films of isotactic polypropylene, high-density polyethylene and ethylene-propylene (EP) copolymers were sterilised under gamma-radiation with doses of 10 and 25 kGy. Neat and sterilised samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and chain scission in polymer chains were characterized by FTIR spectroscopy, SEM and viscometric measurements, respectively. A gradual decrease in intrinsic viscosity [eta] and increase in carbonyl and hydroxyl regions in FTIR spectra were found for the gamma-sterilised samples as a function of increasing dose. Polypropylene was found to be more susceptible to both radio-oxidation and biodegradation. It was observed that in case of ethylene-propylene copolymers, extent of gamma-sterilisation and/or biodegradation depends on the composition and distribution of comonomers. Important surface erosion was detected by SEM, for higher sterilisation doses, after composting. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; chain scission; Composting and fungal culture; gamma-sterilisation; Polyolefins

Characterization of polydimethylsiloxane rubber upon photochemical, thermal, salt-fog ageings and exposure to acid vapours - Delor-Jestin, Florence; Tomer, N. S.; Singh, R. P.; Lacoste, Jacques (E-Polymers, 2006)
The changes in the chemical structure and the physical properties of a filled crosslinked polydimethylsiloxane rubber were monitored as a function of various ageing factors. The variables included photochemical, thermal, salt-fog ageings and exposure to acid vapours. Unaged and aged samples were studied by IR spectroscopy, hardness measurements, Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA) coupled with IR spectroscopy. No significant oxidation was detected after all ageings, except for nitric acid treatment. The presence of aluminium trihydrate was clearly identified as responsible for the observed chemical changes. Then an important vulnerability of this filled silicone rubber towards the cross-linking reactions provoked by usual ageings was also detected. The DSC-thermoporosimetry measurements of the mesh size distribution gave a comparison of cross-linking densities for each ageing. The complementary analysis with TGA-IR allowed us to differenciate the thermal stability of the formulation after various ageings and to acquire new knowledge about thermal decomposition.

Photo-bio-degradability of agro waste and ethylene-propylene copolymers composites under abiotic and biotic environments - Kumar, A. Pratheep; Pandey, Jitendra K.; Kumar, Bijendra; Singh, R. P. (Journal of Polymers and the Environment, 2006)
Composites were prepared by two methods, (i) graft copolymerization (GFC) of isotactic polypropylene (PP) with maliec anhydride, (MAH) followed by esterification with coir fiber and (ii) by direct reactive mixing (DFC) of polypropylene (PP) and ethylene-propylene (EP) copolymers with MAH and peroxide with coir fiber. These composites, after molding in films (5 x 5 cm, - 100 mu m thickness) were examined for susceptibility to biological attack by measuring the percentage weight loss in compost upto 6 months, periodically, and fungal colonization on surface of the samples, when kept as sole carbon source for the growth of Aspergillus niger in culture medium upto 40 days. Photodegradation was evaluated by monitoring the variations in FT-IR spectrum and crack formation after successive treatment with UV light (>= 290 nm) for 0, 20, 50 and 100 h at 60 C in the presence of air. Specimens of virgin PP were taken as a reference during all period of photo and biodegradation studies. Significant changes were observed depending on the preparation methods during photodegradation and biodisintegration of composites. DFCs samples were disintegrated faster than GFCs during the composting whereas, in culture, GFCs were covered highly in well uniform way by fungi. It was observed that photo-oxidative ageing directly enhanced the biodegradability of composites as the increase in fungal growth rate and decrease in weight during composting were found. It was concluded that extent of compatibilization had a profound effect on photo-oxidation and biodisintegration of composite material; consequently ester bonds were main units during fungal consumption. Composition of monomers in copolymers was also showing significant effect on the degradability which decreased with increasing content of ethylene in ethylene-propylene (EP) copolymers.
Keywords: Biodegradation; biodisintegration and composting; composites; ethylene-propylene copolymers; photo-degradation

Photooxidation of vulcanized EPDM/montmorillonite nanocomposites - Morlat-Therias, Sandrine; Fanton, Elisabeth; Tomer, Namrata S.; Rana, Sravendra; Singh, R. P.; Gardette, Jean Luc (Polymer Degradation and Stability, 2006)
The photooxidation of a vulcanized ethylene-propylene-diene monomer (EPDM)/montmorillonite nanocomposite as well as EPDM/nanocomposite with stabilizers was studied under accelerated UV-light irradiation (lambda >= 300 nm, 60 degrees C) for different times. The development of functional groups during oxidation was monitored by infrared spectroscopy. Photodegradation of the neat polymer and composites took place and the increases of absorbance in hydroxyl and carbonyl groups with irradiation times and also the decreases of the EPDM unsaturations were measured. The data indicated that the photooxidation products were not changed in the presence of the nanofiller. However, the presence of MMt was observed to dramatically enhance the rate of photooxidation of EPDM with a shortening of the oxidation induction time, leading to a decrease of the durability of the nanocomposites. On the other hand, it was observed that addition of stabilizers, either Tinuvin P or 2-mercaptobenzimidazole, was efficient in inhibiting the degradative effect of MMt. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: EPDM; Nanocomposite; photooxidation rate; stabilization

Preparation and performance evaluation of EPDM nanocomposites under accelerated weathering - Rana, Sravendra; Tevtia, Amit K.; Kumar, Bijendra; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2006)
The degradability of ethylene propylene diene monomer (EPDM) nanocomposites, prepared from organically modified montmorillonite (CMMT), is studied under accelerated UV irradiation (lambda >= 290 nm) for different time intervals. The development of functional groups during degradation is monitored by FT-IR spectroscopy whereas, surface changes are studied by scanning electron microscopy (SEM). The effect of clay modifier and clay concentration on the degradability are studied. The degradation of neat polymer and composites taking place traditionally and an increase in carbonyl and hydroxyl groups are observed with irradiation time. Neat EPDM is found to be less degradable than nanocomposites. Degradation products, as seen by FT-IR in nanocomposites are found to be the same as in neat polymer but are generated at a faster rate. According to the experimental results, one can define that both ammonium ion and neat montmorillonite (MMT) accelerate the photo-oxidation of EPDM.
Keywords: carbonyl index; Degradation; EPDM; layered silicates; Nanocomposites; photooxidation

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Tevtia, Amit K.; Singh, R. P. (Polymer Degradation and Stability, 2006)
The stabilization of polyolefins against gamma-sterilization has been studied with single or binary additive system. The present attempt is to utilize synergistic mixtures of stabilizers which are approved for food contact applications. Ethylene-propylene (EP) copolymer has been melt-mixed with hindered amine stabilizers (HAS), phenolic antioxidants and organo-phosphites (hydroperoxide decomposer). Samples were sterilized with different doses of gamma-radiation. Stabilization was characterized in terms of changes in the functional groups (oxidation products), tensile properties, yellowing and surface morphology by FTIR spectroscopy, Instron, colorimetry (reflectance) and scanning electron microscopy (SEM), respectively. Results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol system. Among phenol containing systems, where we mostly observe discoloration due to the oxidation of hindered phenol and the combination of secondary HAS, tertiary HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The mixture of secondary HAS and tertiary HAS, has shown antagonistic effect of stabilization whereas their combination with organo-phosphite has exhibited synergistic effect of stabilization even at higher doses of gamma-sterilization. The effects have been explained through the interaction between the stabilizers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Antioxidants; discoloration; ethylene-propylene copolymer; gamma-sterilization; stabilization; tensile properties

Cross-linking assessment after accelerated ageing of ethylene propylene diene monomer rubber - Tomer, N. S.; Delor-Jestin, Florence; Singh, R. P.; Lacoste, Jacques (Polymer Degradation and Stability, 2007)
The ageing of filled and cross-linked ethylene propylene diene elastomer (EPDM) has been studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C, thermal ageing at 100 degrees C and in nitric acid vapours for different time intervals. Hardness measurements were performed. DSC-thermoporosimetry was used to estimate the mesh size distribution and cross-linking densities for each ageing. The development of functional groups was monitored by ATR spectroscopy. An increase in oxidation with exposure time after the different types of ageing was observed. The thermal stability of EPDM was assessed by TGA and evolved volatile gases were identified using FTIR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ageing; EPDM; Oxidation; thermal analysis; thermoporosimetry

Photodegradation of ethylene/propylene/polar monomers, Co-, and terpolymers. II. prepared by Ni catalyst systems - Fernandes, Susete N.; Correia, Sandra; Matos, Ines; Marques, Maria M.; Rana, Sravendra; Kumar, Bijandra; Gupta, M. K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
The copolymers of ethylene/propylene as well as their terpolymers with polar monomers were prepared by Ni-catalyst systems and their photodegradation behavior was studied by Fourier transform infrared spectroscopy. The polar monomers used to synthesize co- and terpolymers of ethylene/propylene/polar monomer were 5-hexen-1-ol, 10-undecen-1-ol, acrylamide, methylmethacrylate, acrylonitrile, and methylvinyl ketone. The morphological changes of the irradiated samples were determined by scanning electron microscopy. The photodegradation kinetics has also been studied. The surface damage caused by polychromatic irradiation (lambda >= 290 nm) at 55 degrees C in atmospheric air is presented in different micrographs. The rate of photo-oxidative degradation is very fast in terpolymers containing polar monomers as compared with copolymers and homopolymers. The morphological study of the photodegraded samples showed a very good correlation with the photodegraded results. (c) 2007 Wiley Periodicals, Inc.
Keywords: copolymerization; Ethylene; Photodegradation; polar monomers; propylene

Photo-oxidation of EPDM/layered double hydroxides composites: influence of layered hydroxides and stabilizers - Kumar, B.; Rana, S.; Singh, R. P. (Express Polymer Letters, 2007)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/layered double hydroxide (LDH) composites as well as EPDM/LDH with stabilizers is studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C for different time intervals. The development of functional groups during oxidation was monitored by FT-IR spectroscopy. The photo-degradation of the pristine polymer and composites take place and the increase in hydroxyl and carbonyl groups with irradiation times, was estimated. EPDM filled LDH showed higher degradation rate than pristine EPDM, while in acidic medium EPDM/LDH showed almost equal degradation as in isolated conditions. These results show the advantages of LDHs as a filler as well as an acid killer. The effect of stabilizers is very less because of their concentration in comparison of LDH.
Keywords: EPDM; layered double hydroxides; Photo-oxidation; polymer composites

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers. part II. polypropylene matrix - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2007)
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis and characterization of hindered amine light stabilizers based on end functionalization of polypropylene - Reddy, K. Raghunatha; Kumar, Bijendra; Rana, Sravendra; Tevtia, Amit K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
A polymeric hindered amine light stabilizer (HALS), where HALS moiety was attached at the terminal end of the polypropylene chain via end-functionalized vinylidine PP through simple organic reactions, was synthesized. It comprises the synthesis of vinylidine-terminated polypropylene by using Cp2ZrCl2/MAO as catalyst system and epoxidation of vinylidene polypropylene. The final product was synthesized by carrying out the reaction between epoxy end functionalized polypropylene and 4-amino-2,2,6,6-tetrametyl piperidine. The final product was characterized by using H-1 NMR, C-13 NMR, and FT-IR spectra. Functionality was calculated by using vapor phase osmometry and H-1 NMR. The solubility and diffusion coefficient of the product were calculated and also its stabilization performance was checked. (c) 2007 Wiley Periodicals, Inc.
Keywords: end functionalization; functionalization of polymers; polymeric HALS; polypropylene; vinylidine and photostabilization

Effect of gamma-dose rate on crystallinity and morphological changes of gamma-sterilized biomedical polypropylene - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2009)
The present work is aimed to study the changes in crystallinity and morphology of biomedical polyolefins after gamma-sterilization. The isotactic polypropylene (iPP) films were sterilized by gamma-radiation and the changes were characterized by differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and atomic force microscopy (AFM) techniques. The effect of dose rate on crystallinity changes also was focused. It was found that crystallinity and morphology significantly changed with gamma-irradiation. There was an increase in crystallinity Lip to 10 kGy accompanied with decrease in viscosity and mechanical properties. The changes in crystallinity mainly depend on gamma-irradiation dose and dose rate. The rise in crystallinity was attributed to chain scission and forming new perfect lamellae. However, the reduction was accompanied by occurrence of gamma- and beta-phases and crosslinking. Possible explanations for transitions in phases are also discussed based on our results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crystallinity; Dose rate; Gamma radiation; mechanical properties; Morphology; polypropylene

Isothermal crystallization and melting behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Singh, R. P. (Thermochimica Acta, 2009)
The effect of layered double hydroxide (LDH) nanolayers on the crystallization behavior of polypropylene (PP) was studied based on the preparation of nanocomposites by a melt intercalation method. The isothermal crystallization kinetics and subsequent melting behavior of PP/LDH hybrids were studied with differential scanning calorimetry (DSC), polarized optical microscopy (POM), and wide-angle X-ray diffraction (WAXD). Studies revealed that the LDH promoted heterogeneous nucleation, accelerating the crystallization of PR The Avrami equation successfully describes the isothermal crystallization kinetics of PP/LDH hybrids and signifies heterogeneous nucleation in crystal growth of PR The varying values of Avrami exponent (n) and half crystallization time (t(1/2)) of PP and PP/LDH hybrids describes overall crystallization behavior. The crystallite size (D(hkl)) and distribution of different crystallites in PP varied in presence of LDH. A significant increase in melting temperature is observed for PP/LDH hybrids. The POM showed that smaller and less perfect crystals were formed in nanocomposites because of molecular interaction between PP chains and LDH. The value of fold surface free energy (sigma(e)) of PP chains decreased with increasing LDH content. Finally, the overall results signify that LDH at nanometer level acted as nucleating agent and accelerate the overall crystallization process of PR (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Isothermal crystallization; Layered double hydroxide; Melting behavior; Polypropylene nanocomposites

Photodegradation of EPDM/MWCNT nanocomposites: effect of singlet oxygen - Kumar, Bijandra; Kumar, Indresh; Singh, R. P. (Polymer Composites, 2009)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/multiwall carbon nanotubes (MWCNT) nanocomposites has been studied under accelerated UV-irradiation (lambda >= 290 nm) in the presence of singlet oxygen. The rate of photodegradation of EPDM/MWCNT is found to be higher when compared to the pristine polymer in presence of singlet oxygen. The enhancement of the rate of degradation of composite has been described through [2 + 2] photocycloaddition reaction between singlet oxygen and double bonds on composite which is followed by cleavage. The rate of degradation and the formation of new functional groups on the composite has been monitored by FTIR spectroscopy and found to be increased with irradiation time. The changes in surface morphology have been studied by scanning electron microscope. Differential scanning calorimetry measurements revealed an increase in the glass transition temperature of photodegraded EPDM and EPDM/MWCNT nanocomposites. POLYM. COMPOS., 30:855-860, 2009. (C) 2008 Society of Plastics Engineers

Preparation and nonisothermal crystallization behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Morlat-Therias, Sandrine; Caperaa, N.; Leroux, Fabrice; Gardette, Jean Luc; Singh, R. P. (Polymer, 2009)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared via melt intercalation using dodecyl sulfate anion modified LDH and maleated PP as compatibilizing agent. Evidently the interlayer anions in LDH galleries react with maleic anhydride groups of PP-g-MA and lead to a finer dispersion of individual LDH layers in the PP matrix. The nanostructure was characterized by XRD and TEM; the examinations confirmed the nanocomposite formation with exfoliated/intercalated layered double hydroxides well distributed in the PP matrix. The nonisothermal crystallization behavior of resulting nanocomposites was extensively studied using differential scanning calorimetry (DSC) technique at various cooling rates. In nonisothermal crystallization kinetics, the Ozawa approach failed to describe the crystallization behavior of nanocomposites, whereas the Avrami analysis and Jeziorny method well define the crystallization behavior of PP/LDH nanocomposite. Combined Avrami and Ozawa analysis (Liu model) also found useful. The results revealed that very small amounts of LDH (1%) could accelerate the crystallization process relative to the pure PP and increase in the crystallization rates was attributed to the nucleating effect of the nanoparticles. Polarized optical microscopy (POM) observations also support the DSC results. The effective crystallization activation energy was estimated as a function of the relative degree of crystallinity using the isoconversional analysis. Overall, results indicated that the LDH particles in nanometer size might act as nucleating agent and distinctly change the type of nucleation, growth and geometry of PP crystals. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Layered double hydroxide; Nonisothermal crystallization kinetics; Polypropylene nanocomposites

Effect of gamma-dose rate on biodegradation of gamma-sterilized biomedical polyolefins - Alariqi, Sameh A. S.; Singh, R. P. (Journal of Polymers and the Environment, 2010)
The aim of the present study is to study the effect of gamma-dose rate on the biodegradation of gamma-sterilized polyolefins. Films of isotactic polypropylene, high density polyethylene and ethylene-propylene (EP) copolymer were sterilized under gamma-radiation with doses of 10 and 25 kGy. Two different (60)Co sources were used with dose rate 600 and 780 Gy h(-1). Neat and sterilized samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and intrinsic viscosity in polymer chains were characterized by FT-IR spectroscopy, SEM and viscometric measurements, respectively. It was observed that both gamma-degradation and biodegradation processes depend on the dose rate of gamma-source. It was found that the biodegradation of gamma-sterilized polyolefins in composting and microbial culture environments increased with decreasing the gamma-dose rate.
Keywords: Biodegradation; Composting and fungal culture; gamma-Dose rate; Polyolefins; Sterilization

Gamma-initiated oxidation of isotactic polypropylene: effect of gamma-dose rate on durability - Alariqi, Sameh A. S.; Singh, R. P.; Rao, B. S. M. (Arabian Journal for Science and Engineering, 2011)
The effect of gamma-irradiation dose rate on the chemical, molecular, and mechanical properties of isotactic polypropylene (iPP) films was investigated using three different Co-60 sources with dose rates of 600, 660, and 780 Gy h(-1). Fourier transform infrared spectroscopy coupled with chemical derivatization with NO and SF4, and measurements of the elongation at break, toughness, and molecular weight were used to describe the effects of gamma-dose rate on iPP. It was found that the formation of oxidation products depended significantly on the dose rate. However, the kinetic accumulation of ketones were more sensitive to the dose rate of gamma source. Degradation induced by gamma-radiation depends on the dose rate-the degradation of mechanical properties was more significant at a low dose rate than at a high dose rate. It was found that the lower the dose rate, the higher the degree of oxidation in terms of the formation of gamma-products. The mechanism of gamma-degradation is discussed based on the correlation between the changes in chemical and physical properties upon exposure to gamma-radiation.
Keywords: Chemical and physical properties; Dose rate; gamma-irradiation; polypropylene

Studies on the feasibility of recycled polystyrene doped with NLO active meta-Nitroaniline for optoelectronics applications - Sureshkumar, M. S.; Goyal, R. K.; Negi, Y. S.; Pratheepkumar, A.; Reddy, K. Raghunatha; Singh, R. P.; Dadge, Jagdish W.; Aiyer, Rohini C. (Polymers for Advanced Technologies, 2011)
A Guest-Host system based on meta-Nitroaniline (m-NA) and recycled polystyrene (RPS) susceptible to generate nonlinear optically (NLO) active property such as second harmonic generation (SHG) has been prepared. Pure, sublimed, optical grade, crystalline m-NA is used as a guest and RPS from the disposable packaging waste as available utilized as the host polymer. In this paper we report the effect of NLO active m-NA on the bulk and optical properties of RPS. The purified m-NA was incorporated from 1-10 wt% in the RPS polymer matrix by conventional solution casting method. Thin, transparent, freestanding films obtained were characterized with optical microscope, scanning electron microscope (SEM), viscosity measurement, and UV-Visible (UV-Vis) spectroscopy for bulk properties evaluation and Nd:YAG laser studies for optoelectronics application such as SHG through frequency doubling. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: frequency doubling; guest-host NLO systems; meta-Nitroaniline; nonlinear optical activity; Polystyrene; second harmonic generation

Self photostabilizing UV-durable MWCNT/polymer nanocomposites - Lonkar, Sunil P.; Kushwaha, Omkar S.; Leuteritz, Andreas; Heinrich, Gert; Singh, R. P. (RSC Advances, 2012)
A potentially active hindered amine light stabilizer (HALS) was successfully anchored onto multiwalled carbon nanotubes (MWCNTs) and used as a light-stabilizing yet reinforcing multifunctional nanofiller to obtain UV-durable polymer nanocomposites. The influence of such light stabilizing MWCNTs on the photo-oxidation behaviour and structure-properties of polypropylene (PP) was studied. The composites were prepared by solution mixing of MWCNTs followed by melt compounding with polypropylene (PP). The resulting composite exhibits excellent UV-durability showing an almost 20 fold increase in the induction period of photo-oxidation. Moreover, the hydrophobic HALS was found to be compatibilizing enough to achieve homogeneous dispersion of exfoliated nanotubes into a polymer matrix. The rheological characterizations predict the formation of a percolated network structure. The obtained nanocomposites present markedly improved mechanical properties which underline the reinforcing ability of functionalized MWCNTs. Overall combination of HALS and MWCNTs offers an attractive route to combine multifunctionality into new hybrid UV-durable polymer nanocomposites. Such materials may possess great potential for outdoors high performance applications.

Synthesis and characterization of a new diol-functionalized s-triazine-based polymerizable hindered amine light stabilizer - Mehare, Rupali S.; Lonkar, Sunil P.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2012)
A new diol-functionalized triazine-based polymerizable hindered amine light stabilizer (HALS) was synthesized in two steps. First, selective synthesis of an s-triazine containing two HALS moieties as substituents was accomplished by using phase-transfer catalysis. This step required the establishment of optimum reaction conditions (type of two-phase system, best solvent, and catalyst). In the second step, the substituted triazine was treated with diethanolamine to introduce polymerizable diol functionality. The resulting product should act as a light stabilizer, since it contains two HALS moieties anchored to a thermally stable s-triazine unit. Moreover, incorporation of the diol into a polymeric material might be expected to impart prolonged stability in weathering environments. Characterization of the diol was accomplished by using Fourier transform infrared spectroscopy (FTIR), `H NMR, and mass spectrometry. J. VINYL ADDIT. TECHNOL., 18:204208, 2012. (c) 2012 Society of Plastics Engineers

Copolymerization of ethylene with unsaturated alcohols and methylmethacrylate using a silylated alpha-diimine nickel catalyst: molecular modeling and photodegradation studies - Matos, Ines; Fernandes, Susete N.; Liu, Hua-Rong; Tevtia, Amit K.; Singh, R. P.; Manda, Lemos; Lemos, Francisco; Marques, Maria M. (Journal of Applied Polymer Science, 2013)
In this article, the experimental results obtained in the copolymerization of ethylene with polar monomers using a silylated -diimine nickel catalyst are described and compared with those obtained with a non-silylate similar one. The results show that the introduction of a siliyl group in the para-position of the imine moiety turns the catalyst less sensitive toward polar functionalities. However, the reactivity observed in copolymerization reactions was found to be reduced both the global polymerization and incorporation rates. Molecular modeling calculation allowed us to understand both the preferred insertion mode and the intermediate product structures for E/MMA copolymerization. Photodegradation studies showed that the presence of polar groups in the copolymers increases their rate of oxidation and turn them more easily degradable. The stabilization performed by Tinuvin 770 showed that for long-exposure times, it is not very effective regardless it is only mixed or grafted to the copolymer. (c) 2012 Wiley Periodicals, Inc.
Keywords: ageing; copolymers; Degradation; grafting

Preparation and characterization of self-photostabilizing UV-durable bionanocomposite membranes for outdoor applications - Kushwaha, Omkar S.; Avadhani, C. V.; Singh, R. P. (Carbohydrate Polymers, 2015)
Here, we report a durable and ultraviolet (UV) resistant nanocomposite membrane of chitosan (CS) with effective photostabilization ascribed to Zinc oxide (ZnO) nanoparticles. Zinc oxide nanoparticles were successfully dispersed in the solution of chitosan polymer. The nanocomposite films with the homogenous dispersion of ZnO nanoparticles in the chitosan matrix were obtained by solution casting method and the influence of ZnO nanoparticles as a photostabilizer was studied. The nanocomposite membranes were photoirradiated by polychromatic radiations with lambda > 300 nm using mercury vapour lamps in SEPAP instrument. The resulting nanocomposite material exhibited excellent UV-resistance in very low percentages of ZnO nanoparticles. The chitosan membranes showed fast degradation attributes than the nanocomposite membranes. ZnO nanoparticles effectively absorbed UV radiations, thus protecting polymer from radiation degradation. The neat and irradiated nanocomposites of chitosan and ZnO nanoparticles (CS/ZnO) were characterized by Fourier Transform Infrared Spectroscopy (FT-IR) spectroscopy for the chemical changes/degradation taking place. Chitosan nanocomposites were further characterized for tensile properties, contact angle measurements and surface morphology. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bionanocomposite membrane; Chitosan; Contact angle measurement; Fourier transform infrared spectroscopy; Photostabilization; Zinc oxide nanoparticles